Antihistamines or decongestants for otitis media with effusion—do they work?. Issue 2 (7th March 2013) - Cohen, Eyal
Abstract Eco‐paediatrics is an occasional feature in Evidence‐Based Child Health: A Cochrane Review Journal. Our goal is to contribute to the worldwide discussion on reducing waste in health care. In each instalment, we will select a recent Cochrane review highlighting a practice, still in use, which the available evidence tells us should be discontinued.